Becoming A Whole Human: Qur'an Perspective Letter At Tiin: 4 And Letter Ad Dzariyat: 56 - Cindy Fatika Sary; Anisya Astanti Utomo; Didik Himmawan (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
The aim of this research is to understand in more detail the nature of humans, the position of humans, human responsibilities, the characteristics of humans in the Qur'an, the purpose of human life in the Qur'an and the process of creating humans as creatures of Allah Swt. So that it can be known that humans are creatures of Allah Swt. which consists of a spirit and body equipped with potential and advantages compared to Allah Swt. creatures. others, namely the heart, mind and body. The author uses qualitative research methods, so this research will produce information that provides a comprehensive and clear picture of how to be a complete human being. From research conducted by the author with the title "Becoming A Whole Human: Qur'an Perspective Letter At Tiin: 4 and Letter Ad Dzariyat: 56". Based on the data obtained, the author concludes that there are still many people who feel inadequate and inferior about what Allah Swt. has given them. bestowed upon him, even though Allah Swt. confirm in the Qur'an Surah At Tiin: 4 that Allah Swt. has created humans in excellent form. And for the negligence of humans who are too proud in the world, until they forget their obligations in carrying out worship to Allah SWT.